Clinical Outcome for Lumbar Disc Herniation Treatment with Intradiscal Oxygen-ozone Therapy - Yadav, Rupesh Kumar; Sherpa, Tshering; Hamal, Pawan Kumar; Pokhrel, Nabin; Thakur, Jay Prakash; Amatya, Shirish Prasad; Piya, Roshan (Journal of Nepal Health Research Council, 2024)
Background: Low back pain due to disc herniation is a common problem causing frequent hospital visits and loss of working days with major socio-economic impact. Conservative treatments like analgesics, physiotherapy do not work in all patients. Surgical treatment has been main stay of treatment when indicated but is associated with anesthetic and surgical complications. Intradiscal oxygen-ozone chemonucleolysis is minimum invasive procedure done under local anesthesia and has promissing role in shrinking the bulged disc and reducing nerve root compression and related symptoms. This retrospective study was done to see how intradiscal oxygen-ozone chemonucleolysis reduces the pain severity in patient with discogenic low back pain.Methods: Retrospective data were retrieved of those patients who underwent fluoroscopy guided intradiscal oxygen-ozone chemonucleolysis with 5-6 ml of an O2-O3 mixture (concentration of 30 microgram/ml) during the period of two years in Nepal pain care and research center. Numerical pain scale (NRS) at various follow ups were compared to preprocedural NRS.Results: Preprocedural NRS was 8± 1. NRS at three hours, one week, one month, three months and six months were 2± 0.3 (73.44 percent reduction), 2.5± 2 (68.85 percent reduction), 2.3± 2 (72.13 percent reduction), 1.8± 1.7 (77.87 percent reduction) and 1.67± 1.4 (79.51 percent reduction) respectively.Conclusions: Intradiscal oxygen-ozone chemonucleolysis can be useful modality of treatment for discogenic low back pain when failed to respond to the conservative management and in whom surgery is not indicated. Keywords: Chemonucleolysis; disc prolapse; fluoroscopy; low back pain; ozone.